Analisis Pemahaman Konsep Terhadap Mata Pelajaran IPS Materi Barter pada Siswa Kelas III di SD Negeri 091 Palembang - Yusnia, Sarah; Heldayani, Eni; Jayanti, Jayanti (Indonesian Research Journal on Education, 2022)
This study aims to determine the extent to which the understanding of the concept of social sciencesubjects on bartering material in third grade students. The research method used in this research is descriptive qualitative. Data collection techniques used by researchers in this study wereobservation, interviews and documentation. The data obtained were then analyzed using a qualitative descriptive research method. The results of this study indicate that the level ofunderstanding of students' concepts of social studies subjects, especially barter material for third grade students at SD Negeri 091 Palembang, is included in the good category. This can be proven from the results of the evaluation conducted by researchers on students' understanding of concepts in the social studies subject of bartering material, there are 8 (eight) students in the very good category (36,38%), 7 (seven) students in the good category (31,81% ) and 7 (seven) students in the sufficient category (31,81%) with a total of 22 (twenty two) students.